2015
DOI: 10.1098/rstb.2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

Individual participation in intergroup contests is mediated by numerical assessment strategies in black howler and tufted capuchin monkeys

Abstract: One contribution of 13 to a theme issue 'Solving the puzzle of collective action through inter-individual differences: evidence from primates and humans'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 83 publications
(128 reference statements)
1
25
1
Order By: Relevance
“…Van Belle & Scarry [37] observed communal defence in wild black howler (Aloutatta pigra) and tufted capuchin monkeys (Sapajus nigritus). They find that both species rely on assessment of numerical asymmetry in male group size (rather than total group size) when deciding to participate in communal defence.…”
Section: Ecology Group Size and Anticipated Benefitsmentioning
confidence: 99%
“…Van Belle & Scarry [37] observed communal defence in wild black howler (Aloutatta pigra) and tufted capuchin monkeys (Sapajus nigritus). They find that both species rely on assessment of numerical asymmetry in male group size (rather than total group size) when deciding to participate in communal defence.…”
Section: Ecology Group Size and Anticipated Benefitsmentioning
confidence: 99%
“…In the case of intergroup conflict, RHP can be operationally defined as group size, but the individual attributes of the group members may also play a part in determining competitive ability. Van Belle and Scarry (2015) found that black howler monkeys (Alouatta pigra) increased their participation in inter-group interactions when male group sizes were equal. Human intergroup contests can be analysed using a similar conceptual framework.…”
Section: Introductionmentioning
confidence: 99%
“…Although group size may establish the maximum possible RHP of a group by setting an upper limit on the number of coalitionary partners available, the realized RHP is determined by the number of individuals participating in the current contest. Variation in the context of an encounter may cause dyadic asymmetries in the number of participating individuals to fluctuate (e.g., Crofoot & Gilby, 2012;Koch, Signer, Kappeler, & Fichtel, 2016) either because individuals have different thresholds of participation (e.g., Arseneau-Robar, Taucher, Schnider, van Schaik, & Willems, 2017;Heinsohn and Packer, 1995;Kitchen, 2004;Kitchen, Horwich, & James, 2004;Van Belle & Scarry, 2015) or because individuals pursue disparate strategies during a single encounter (e.g., Arseneau-Robar, Taucher, van Schaik, & Willems, 2015, Koch et al, 2016. Moreover, when individual participation in intergroup aggression produces collective benefits that are shared with nonparticipating individuals (e.g., through home range exclusivity: Willems, Arseneau, Schleuning, & van Schaik, 2015), free-riding can create a disconnect between the maximum and realized RHP (Olson, 1965;Van Schaik, 1996;Nunn, 2000;Kitchen, 2004;Kitchen et al, 2004;Kitchen, 2006;Bonanni, Valsecchi, & Natoli, 2010;Harris, 2010;Crofoot & Gilby, 2012;Koch et al, 2016).…”
mentioning
confidence: 99%
“…Among Argentine tufted capuchin monkeys (Sapajus [Cebus apella] nigritus), although decided dominance relationships are apparent between most group dyads (Scarry, 2013), individuals frequently initiate and participate in aggressive encounters with dominant neighbors (Van Belle & Scarry, 2015). Within this population, male group size is the critical measure of a group's competitive ability, predictably determining the outcome of aggressive encounters (Scarry, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation